17β-Estradiol sensitizes ovarian surface epithelium to transformation by suppressing Disabled-2 expression - Vuong, Nhung H.; Salah Salah, Omar; Vanderhyden, Barbara C. (Scientific reports, 2017)
Estrogen replacement therapy increases the risk of human ovarian cancer and exogenous estradiol accelerates the onset of ovarian cancer in mouse models. This study uses primary cultures of mouse ovarian surface epithelium (OSE) to demonstrate that one possible mechanism by which estrogen accelerates the initiation of ovarian cancer is by up-regulation of microRNA-378 via the ESR1 pathway to result in the down-regulation of a tumour suppressor called Disabled-2 ( Dab2 ). Estrogen suppression of Dab2 was reproducible in vivo and across many cell types including mouse oviductal epithelium and primary cultures of human ovarian cancer cells. Suppression of Dab2 resulted in increased proliferation, loss of contact inhibition, morphological dysplasia, and resistance to oncogene-induced senescence – all factors that can sensitize OSE to transformation. Given that DAB2 is highly expressed in healthy human OSE and is absent in the majority of ovarian tumours, this study has taken the first steps to provide a mechanistic explanation for how estrogen therapy may play a role in the initiation of ovarian cancer.